(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
Blood Samples were kept at different temperature for a period of 3 months to know the amount of quantitative DNA recovery from these samples in different conditions of temperature and ageing [Time]. The DNA isolation was done by standard phenol-chloroform method and optical density of the isolated DNA was measured by spectrophotometer. Recoverable DNA was found in all samples even after 3 months of study however the amount of DNA recovery decreased with time which is more marked in the initial phase followed by a slow and uniform decrease in DNA yield. Mean DNA yield at zero time at room temperature from fresh blood samples was found to be 1027± 361 μg/ml. Minimum and maximum yield was found to be 432.7 μg/ ml and 1655 μg/ml respectively.